Cell-in-cell structures are more potent predictors of outcome than senescence or apoptosis in head and neck squamous cell carcinomas - Schenker, Hannah; Buettner-Herold, Maike; Fietkau, Rainer; Distel, Luitpold (Radiation Oncology, 2017)
This study sheds light on cell inactivating processes with focus on the phenomenon of cell-in-cell (CIC). Cell-in-cell describes a cell process where one cell is being engulfed by another non-professional phagocyte. We determined frequency and prognostic impact of CIC structures (CICs) as well as of senescent and apoptotic cells in head and neck squamous cell carcinomas (HNSCC).These different forms of cell inactivation as well as the proportion of proliferating and tumor cells were assessed in 169 pre-radiochemotherapy biopsies and 32 post-therapy tumor resections by immunohistochemistry of tissue microarrays. Four consecutive cancer sections were stained with antibodies specific for E-cadherin for CIC detection, cleaved caspase-3 for apoptosis, H3K9Me for senescence and Ki67 as a proliferation marker. Positive events were quantified in corresponding tumor areas.CICs were found in 55.5%, senescent cells in 67.1% and apoptotic cells in 93.3% of samples. While no prognostic impact of apoptotic and senescent cells was observed, CICs turned out to significantly influence overall-survival (p = 0.016) with a lack of CICs being prognostically beneficial. There was no correlation between CICs and apoptosis and 98.9% of CICs were negative for cleaved caspase-3.CIC formation is a frequent event in HNSCC and a superior predictive marker compared to senescence and apoptosis. Independence of CIC and apoptosis and the adverse prognosis associated with numerous CICs lead to the assumption that CICs might take up necrotic rather than apoptotic cells preventing an adequate antitumoral immune response that would otherwise be initiated by necrotic cells through damage-associated molecular pattern molecules.
EVALuna2:25527